Landscape of buildings on a rolling hill. All the buildings are white, one is a church and others appear to be barracks, Fort Chippewyan, Alberta. Note on the front reads: "Ft. Chippewyan Lake Athabasca". Note on the back reads: "All Hudson Bay property" (1899)
Hudsons Bay Company - - Forts and trading posts; Hudsons Bay Company - - Stores; Land settlement; Buildings